Implementasi SCM Pada Pengelolaan Bahan Baku Dan Distribusi Pomade Berbasis Web (Studi Kasus : Tomik Pomade) - Deppy Pahrudinsyah; Aji Permana (Sistem Informasi Fakultas Ilmu Komputer Universitas Kuningan, 2020)
SCM Implementation On Raw Material And Pomade Distributor management is a form of information technology strategy that can assist in managing production data and stock provision, while its development model is using Supply Chain Management model. Supply Chain Management is a set of approaches that is used to effectively integrate suppliers so that inventory can be produced and distributed at the right amount, to the right location, and at the right time so that the overall cost of the system can be minimized. The design system uses waterfall method, the tools used to design the system are in the form of Flow Map (document flow chart), Context Diagram, DFD (Data Flow Diagram), ERD, and Table Relationships while data collection techniques use observation, interviews, and literature study. This application is built using PHP programming language and MySQL for database. Using this system, it is expected to facilitate the factory staff at Tomik Pomade in managing production and inventory.